Does expanding higher education reduce income inequality in emerging economy? Evidence from Pakistan - Qazi, Wasim; Raza, Syed Ali; Jawaid, Syed Tehseen; Abd Karim, Mohd Zaini (Routledge, 2018)
This study investigates the impact of development in the higher education sector, on the Income Inequality in Pakistan, by using the annual time series data from 1973 to 2012.The autoregressive distributed lag bound testing co-integration approach confirms the existence of long-run relationship between higher education and income inequality.Results indicate that higher education has a negative and significant relationship with the income inequality in the long run, while a negative but insignificant effect is found in the short run.Results of cumulative sum (CUSUM) and CUSUM of square test suggest that there is no structural instability in the residuals of equation of income inequality.Results of causality analyses confirm the unidirectional causal relationship between higher education development and income inequality in Pakistan, which runs from the higher education development to the income inequality.The findings of this study suggest that development in the higher education sector would be a significant policy option to control the income inequality and should be considered a means to improve the income distribution in Pakistan.